A phase I first‐in‐human study with tefinostat – a monocyte/macrophage targeted histone deacetylase inhibitor – in patients with advanced haematological malignancies. (7th May 2013) - Ossenkoppele, Gert J.; Lowenberg, Bob; Zachee, Pierre; Vey, Norbert; Breems, Dimitri; Van de, Arjan A.; Davidson, Alan H.; Wells, Graham; Needham, Lindsey; Bawden, Lindsay; Toal, Martin; Hooftman, Leon; et al.
Summary Tefinostat (CHR‐2845) is a monocyte/macrophage targeted histone deacetylase inhibitor (HDACi). This first‐in‐human, standard 3 + 3 dose escalating trial of oral, once daily tefinostat was conducted to determine the safety, tolerability, pharmacokinetic and pharmacodynamic profile of tefinostat in relapsed/refractory haematological diseases. Eighteen patients were enrolled at doses of 20–640 mg. Plasma concentrations of tefinostat exceeded those demonstrated to give in vitro anti‐proliferative activity. Flow cytometric pharmacodynamic assays demonstrated monocyte‐targeted increases in protein acetylation, without corresponding changes in lymphocytes. Dose‐limiting toxicities (DLTs) were not observed and dose escalation was halted at 640 mg without identification of the maximum tolerated dose. Drug‐related toxicities were largely Common Toxicity Criteria for Adverse Events grade 1/2 and included nausea, anorexia, fatigue, constipation, rash and increased blood creatinine. A patient with chronic monomyelocytic leukaemia achieved a bone marrow response, with no change in peripheral monocytes. An acute myeloid leukaemia type M2 patient showed a >50% decrease in bone marrow blasts and clearance of peripheral blasts. In conclusion, tefinostat produces monocyte‐targeted HDACi activity and is well tolerated, without the DLTs, e.g. fatigue, diarrhoea, thrombocytopenia, commonly seen with non‐targeted HDACi. The early signs of efficacy and absence of significant toxicity warrant further evaluation of tefinostat in larger studies. (clinicaltrials.gov identifier: NCT00820508).